Fabrication and Evaluation of Sustained Release Mucoadhesive Losartan Potassium Matrix Tablets (Bangladesh Pharmaceutical Journal, 2015)
Sustained release matrix tablets of Losartan potassium were prepared with different types of mucoadhesive polymers e.g. Hydroxypropylmethyl cellulose (HPMC), Sodium carboxymethyl cellulose (Na-CMC) and Methyl cellulose (MC). The tablets were prepared by direct compression method and then were subjected to in-vitro drug dissolution for 8 hours in phosphate buffer of pH 6.8. The mucoadhesive property was investigated in terms of retention time by wash-off method. Irrespective of amount of polymer, mucoadhesive strength of MC was proved to be maximum where HPMC and Na-CMC showed moderate or poor mucoadhesive strength. Drug release from all formulations followed Higuchi release mechanism. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22297 Bangladesh Pharmaceutical Journal 16(2): 153-157, 2013